Implementasi Aplikasi Elektronik Monitoring Esekusi Pembiayaan Hak-Hak Perempuan dan Anak Pasca Perceraian di Pengadilan Agama Bengkulu dalam Perfektif Maslahah Mursalah - Ngadio, Ngadio; Fatimah, Fatimah; Yarmunida, Miti (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstracts: This research aims to achieve four objectives: 1) To explain the implementation of the E-Mosi Caper application at the Bengkulu Religious Court for civil servants in Bengkulu Province. 2) To delineate the obstacles encountered in fulfilling the financial rights of women and children post-divorce (E-Mosi Caper) for civil servants in the Regional Government of Bengkulu Province. 3) To propose solutions for overcoming these challenges faced by civil servants in the Regional Government of Bengkulu Province. 4) To analyze the implementation of the Electronic Monitoring Application for the Execution of Financing the Rights of Women and Children Post-Divorce (E-Mosi Caper) at the Bengkulu Religious Court from the perspective of Maslahah Mursalah and its relevance to the civil servants of Bengkulu Province. The data collection methods employed in this research include interviews, documentation, and observation. The study reveals the following findings: 1) The implementation of the E-Mosi Caper application as a medium for ensuring the provision of alimony for children and wives post-divorce at the Bengkulu Religious Court has been, in essence, running effectively. 2) The key challenge identified is the lack of sufficient socialization regarding the application of E- Mosi Caper. 3) A proposed solution is the broader implementation and utilization of the E- Mosi Caper application. 4) From the perspective of Maslahah Mursalah, the implementation of the E-Mosi Caper application falls under the category of Maslahah al-Hajiyyat (public benefit of necessity), as it facilitates smoothness, ease, and success for individuals in a comprehensive and holistic manner.Keywords: Execution, E-Mosi Caper, Divorce, Maslahah Mursalah, Islamic Law. Abstrak : Tujuan penelitian ada 4 yaitu, 1) menguraikan implementasi E-Mosi Caper di Pengadilan Agama Bengkulu bagi aparatur sipil negara propinsi Bengkulu. 2). Menguraiakn kendala yang dihadapi dalam pemenuhan pembiayaan hak-hak perempuan dan anak pasca perceraian (E-Mosi Caper) bagi Aparatur Sipil Negara Pemerintah Daerah Propinsi Bengkulu. 3). menawarkan solusi yang dihadapi bagi aparatur sipil negara di Pemerintah Daerah Propinsi Bengkulu 4). menganalisis dengan rumusan Maslahah Mursalah terhadap Implementasi Aplikasi Elektronik Monitoring Eksekusi Pembiayaan Hak-Hak Perempuan dan Anak Pasca Perceraian (E-Mosi Caper) di Pengadilan Agama Bengkulu terhadap Aparatur Sipil Negara Propinsi Bengkulu. Metode pengumpulan data menggunakan teknis wawancara, dokumentasi, dan observasi. Penelitian ini menyampaikan bahwa : 1). Implementasi Aplikasi E-Mosi Caper sebagai media pemenuhan nafkah anak dan istri pasca perceraian pada Pengadilan Agama Bengkulu pada dasarnya sudah berjalan dengan baik. 2). Adapun kendala yang penulis temukan dilapangan adalah adalah kurangnya sosialisi terhadap implementasi aplikasi E-Mosi Caper. 3). Menawarkan solusi pemecahan masalah adalah adanya penerapan aplikasi E-Mosi Caper dan 4). Menghasilkan persfektif maslahah mursalah terhadap Implemtasi aplikasi E-Mosi Caper itu termasuk Kategori maslahah al-Hajiyyat karena mendatangkan kelancaran, kemudahan, dan kesuksesan bagi manusia secara utuh menyeluruh.Kata kunci : Eksekusi, E-Mosi Caper, Perceraian, Maslahah Mursalah, Hukum Islam.